(untitled) (International Journal of Management and Sustainability, 2021)
Among the fast-developing economies in the Association of Southeast Asian Nations (ASEAN), a significant trend can be observed towards sustainable energy objectives. Although there is a strong trend of social and economic growth in the ASEAN region, the theoretical and empirical significance of sustainable energy is yet to be explored. This study aims to analyse the impact of sustainable energy on the economies of three countries – Indonesia, Malaysia, and Thailand – using yearly observations from the years 2000 to 2019. Several dynamics of sustainable energy are investigated as explanatory variables, while economic trends are explored through GDP growth, financial development, and patent applications. For the purposes of data analysis, descriptive statistics, correlation matrices and fixed and random effect panel models are applied. The study findings of the correlational matrix indicate that there is no higher correlation among the study variables. The results of the panel models provide evidence that carbon emissions have an adverse impact on GDP growth, while the proportion of renewable energy out of total energy positively impacts the growth dynamic. Additionally, carbon emissions adversely impact financial development in all three ASEAN economies. Lastly, electricity prices and carbon emissions are observed to have an adverse effect on patent applications. However, this study has three major limitations, as it fails to apply advanced panel regression models like GMM, only considers three economies out of the total sample of the ASEAN region, and lacks comparative analyses between countries. Future studies are highly recommended to address these limitations.